2019
DOI: 10.1371/journal.pone.0224765
|View full text |Cite
|
Sign up to set email alerts
|

Identifying resurrection genes through the differentially expressed genes between Selaginella tamariscina (Beauv.) spring and Selaginella moellendorffii Hieron under drought stress

Abstract: Selaginella tamariscina (Beauv.) spring, a primitive vascular resurrection plant, can survive extreme drought and recover when water becomes available. To identify drought-inducible genes and to clarify the molecular mechanism of drought tolerance, a comparative transcriptional pattern analysis was conducted between S. tamariscina and Selaginella moellendorffii Hieron (drought sensitive). 133 drought related genes were identified, including 72 functional genes and 61 regulatory genes. And several drought respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 64 publications
2
7
0
Order By: Relevance
“…Proteomic analysis identi ed many desiccation-responsive proteins in S. tamariscina associated with photosynthesis, antioxidant defense, and translational modi cation (Wang et al 2010). Similar ndings were showed in the study of Gu et al who found that multiple genes involved in antioxidant defense system, polyamine and carbohydrate metabolism, and stress-defensive protein biosynthesis such as dehydrins and aquaporins could contribute to desiccation tolerance of S. tamariscina due to bene cial roles of these metabolites and proteins in antioxidant, OA, and signal transduction (Gu et al 2019). In addition, abscisic acid signaling was one of important desiccation tolerance strategies in S. tamariscina (Liu et al 2008;Xu et al 2018).…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…Proteomic analysis identi ed many desiccation-responsive proteins in S. tamariscina associated with photosynthesis, antioxidant defense, and translational modi cation (Wang et al 2010). Similar ndings were showed in the study of Gu et al who found that multiple genes involved in antioxidant defense system, polyamine and carbohydrate metabolism, and stress-defensive protein biosynthesis such as dehydrins and aquaporins could contribute to desiccation tolerance of S. tamariscina due to bene cial roles of these metabolites and proteins in antioxidant, OA, and signal transduction (Gu et al 2019). In addition, abscisic acid signaling was one of important desiccation tolerance strategies in S. tamariscina (Liu et al 2008;Xu et al 2018).…”
Section: Introductionsupporting
confidence: 83%
“…. It has been reported that enhanced carbohydrate metabolism could be a positive strategy for adaptation to desiccation through comparing differential genes in drought-tolerant S. tamariscina and drought-sensitive S. moellendor i(Gu et al 2019). Desiccation-tolerant S. lepidophylla could also accumulate more sugars and sugar alcohols than desiccation-sensitive S. moellendor i when leaf RWC declined from 100-50%(Yobi et al 2012).…”
mentioning
confidence: 99%
“…superoxide dismutase, peroxidase, catalase and glutathione reductase) and the accumulation of osmolites ( e.g. proline and soluble sugars) to counteract the mechanical and oxidative stresses induced by drought (Xu et al, 2018; Gu et al, 2019). In particular, abscisic acid regulates drought resistance genes in plants and is involved in the accumulation of sugars, the regulation of closure of stomata and in redox balance (Liu et al, 2008; Liu et al, 2019).…”
Section: Looking For ‘Food’ – Between Light and Watermentioning
confidence: 99%
“…Interestingly, LEA-like proteins are also found in a variety of organisms, such as anhydrobiotic nematodes [111,112], brine shrimp [113], rotifers [114,115], and some bacterial species [108]. Although LEAs were first described in embryonic tissues, thirty years of intensive research showed that the expression of LEA genes is also significantly induced in vegetative organs (i.e., callus, flowers, roots, leaves, buds) under abiotic stresses such as desiccation, salinity, and cold [116][117][118][119][120].…”
Section: Late Embryogenesis Abundant (Lea) Proteins Accumulationmentioning
confidence: 99%